Exploring the Molecular Mechanisms of Autophagy-related Genes in Hepatic Ischemia/Reperfusion Injury Using Bioinformatics - Qi Xiao, PhD; Xiaoxiao Hu, MD; Qiong Chen, MD; WenYu Wang, MD; JianSheng Xiao, PhD; Biqi Fu, PhD (Transplantation Direct)
Background. Autophagy is a highly conserved cellular process. In the context of hepatic ischemia/reperfusion injury (HIRI), dysregulation of autophagy may lead to hepatocyte dysfunction. Therefore, we conducted a comprehensive transcriptomics analysis to investigate the biomolecular mechanisms underlying autophagy in HIRI. Methods. Bioinformatics were used to analyze the GSE112713 data set, with the objective of identifying the differential expression of autophagy-related genes (DEARGs). The expression and diagnostic potential of DEARGs were validated using in vitro models and receiver operating characteristic curves. Additionally, potential therapeutic drugs targeting DEARGs were predicted. Results. Transcriptome bioinformatics analysis revealed widespread dysregulation of autophagy in HIRI. Seven DEARGs (IL6, JUN, HSPA1A, PPP1R15A, ERN1, DNAJB1, and HSPA1B) were confirmed in vitro. Based on these findings, we predicted potential drugs that may mitigate HIRI by modulating autophagy. Conclusions. The present study identified 7 DEARGs (IL6, JUN, HSPA1A, PPP1R15A, ERN1, DNAJB1, and HSPA1B) in HIRI, which provides a reliable therapeutic target for HIRI.